The Potential of Chaff Insulation Panel for Sound Absorption and Thermal Properties - Mohd Zizwan, Muhammad Zafri; Mohamed Yusop, Fatimah (Progress in Engineering Application and Technology, 2022)
Rice husk is a common agricultural waste product in places where rice is grown. Rice husk (chaff) is an agricultural waste that is not used and will usually be eliminated by burning. If this potential waste is not handled properly, it might cause environmental problems. This study aims to produce insulating material for the energy conservation of the building. The insulating material was prepared from rice husk by mixing with hydraulic lime (binder). Five sample was prepared with different proportional of rice husk and hydraulic lime by using cold and hot pressed. From that, two samples were selected with the ratio of rice husk to lime are 1:4 (Sample A) and ratio 1:3 (Sample B) for further testing. The sample was then investigated for thermal conductivity and sound absorption coefficient. The result obtained for the Sample A is k = 0.088 W/mK and for Sample B is 0.077 W/mK. For sound absorption coefficient, the results were promising for both samples, especially for high frequencies above 2500 Hz, when the maximum values are 0.82 at 3150 Hz for Sample A and 0.85 at 4000 Hz for Sample B, with noise reduction coefficient equal to 0.33 and 0.24, respectively. The chaff insulation panel have a low thermal conductivity and show a better sound insulation than standard gypsum board which recorded 0.85 sound absorption coefficient at 4000 Hz that is near to 1 which make this product a good insulation panel. In addition, suggestions for the enhancement of future studies and as a reference for future research are provided as comments on this study.